Implementation of Usability Testing for Usability Analysis of Ruang Guru Camp Application for Learning - Khasanah, Dewi; Suryadi, Akmal (Jurnal Riset Ilmu Pendidikan, 2024)
The Ruang Guru Camp application is an application that provides various digital education services that can be accessed by students. The main features of the LMS in Ruangguru Camp include managing learning materials, setting study schedules, and evaluating student learning outcomes, especially for independent study students as product managers. This research was carried out by distributing questionnaires online to users of the Ruang Guru Camp application with a total of 77 respondents. The test method used in this research included validity and reliability tests using SPSS software. The significance of the Alpha value used in this research is 0.05. From the results of data validity tests carried out, all indicators have values above 0.05. From the results of the reliability test, all statements in the questionnaire also have a Cronbach's Alpha value of 0.708, which means all statements are appropriate. The research results show that the application has an average usability of 80.7%, with the highest score in the satisfaction aspect (84.3%) and the lowest in the error aspect (75%). So it can be stated that the Ruang Guru application is good, even though the application is considered good in terms of ease of use and efficiency, there is still room for better development to improve the user experience in the future.